Venoarterial Extracorporeal Membrane Oxygenation for Refractory Cardiogenic Shock in Elderly Patients: Trends in Application and Outcome From the Extracorporeal Life Support Organization (ELSO) Registry - Lorusso R. (Elsevier USA, 2018)
10.1016/j.athoracsur.2016.10.023